Some Features of Classifiers Implementation for Object Recognition in Specialized Computer systems - Abu-Jassar Amer Tahseen; Al-Sharo Yasser Mohammad; Lyashenko, V.; Sotnik, S. (TEM Journal, 2021)
Generalized formalization of recognition algorithm for specialized computer systems is presented in this paper. The structure features of image recognition methods, which have to be taken into account when developing classifiers for object recognition in specialized computer systems, are described. The fundamental types of images characteristics-features, which are used in various methods of image recognition, are discussed. Approaches to development of classifiers for recognizing robotization objects, which are implemented on basis of Haar classifiers, are discussed. The issues of using machine learning algorithm of adaptive gain AdaBoost for development of such classifiers are also considered. Utilities have been developed for implementation of classifiers for object recognition in specialized computer systems.
Keywords: Robotics; image; recognition; semantic network